Caracterização e perspectivas de utilização de escamas da tilápia do Nilo - Vivian, Marisa Maria Pletsch Schneider (2013)
The aquaculture sector should be engaged in proposals that reduce the emission of waste seeking alternatives for managing waste that will be generated, ensuring their growth and sustainability. The objectives were to characterize microbial and determine the the proximate composition, amino acids, macro and micronutrients, heavy metals and pointing technology alternatives for the use of scales of Nile tilapia, Oreochromis niloticus, collected in an industry filleting the western Paraná. The samples of scales were sent to the laboratory for determination of fecal coliforms, total coliforms, Staphylococcus aureus, enterobacteria and Salmonella spp. Analyses of crude protein, ether extract and ash were performed. The total content of amino acid scales was performed using HPLC/UV, after acid digestion. Total concentrations of macronutrients, micronutrients and toxic heavy metals were measured after digestion of the samples and perchloric nitro read by atomic absorption spectrometry and UV-VIS spectrophotometer. The absence of Salmonella spp. was found in 100% of samples. The fecal coliforms, total coliforms and Staphylococcus aureus showed mean values of 1.0 x 101, 4.1 x 101 and 5.0 x 101 CFU/g, respectively. The mean values of crude protein (PB), ether extract and ash were 49.06, 0.22 and 44.51%, respectively. Among the amino acids found in scales include the values of glycine (10.64 g/100 g) and proline (6.78 g/100 g). The amount of calcium (Ca) value was 67.53 g/kg and phosphorus (P) was 33.39 g/kg, given ratio from 1.5 to 2.1 Ca and P. The scales tilapia have contamination enterobacteria and heavy metals (Cd , Cr and Pb), with values above the levels established by law, and may not be used for animal feed, untreated. The results for PB, Ca, P, glycine, proline, among others, in the scales of Nile tilapia, suggest that these can be used as a potential source alternatives for filleting industry. Among the alternatives to the use of the scales, it has been the extraction of collagen and keratin, to use as a filter, fertilizer, substrates and crafts, and also the production of fishmeal and silage. The alternatives presented for use of scales can lead to production and recovery of by-products from this waste of fish, increasing income generation in the industry and reducing the environmental impact